ANALYSIS OF CLASSIFICATIONS OF EUPHEMISMS (Scientific journal of the Fergana State University, 2023)
Drawing the attention of linguists as the specific language units, used instead of taboo words, euphemism were studied in different aspects. The present article elucidates the issues of  characteristics of euphemisms and their classification. As  a multifaceted phenomenon euphemisms are used in various spheres and formed according to different types of word formation. Considering it, there is a range of classifications of euphemisms, which reveal the character of using these language units. The classification of euphemisms makes an impetus to deeply analyzing the nature of  euphemisms.